2011
DOI: 10.1007/s10942-011-0132-6
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism, Coping, Social Support, and Depression in Maltreated Adolescents

Abstract: The current study examined the associations among dimensions of perfectionism, coping, social support, and depression in 58 adolescents with a history of maltreatment. Participants completed the Child-Adolescent Perfectionism, multidimensional measures of coping and social support, and the CES-D Depression Scale. Correlational analyses showed that depression was associated with socially prescribed perfectionism, internalized emotion-oriented coping, avoidant-oriented distancing, and low family support and peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 56 publications
(54 reference statements)
8
43
0
6
Order By: Relevance
“…In addition to research supporting the effects of maltreatment experiences, particularly sexual abuse, on the use of coping strategies (Bal et al, 2003;Hager & Runtz, 2012;Runtz & Schallow, 1997;Sabina & Tindale, 2008), these results indicated that psychologically maltreated adolescents use more maladaptive coping and less adaptive coping. This is consistent with previous studies (Bal et al, 2003;Flett et al, 2012;Hager & Runtz, 2012;Kraaij et al, 2003;Runtz & Schallow, 1997;Sabina & Tindale, 2008;Tremblay et al, 1999). Parent-child relationships play a significant role in the development of coping skills (Lerner et al, 2002), and children learn how to cope with stressful events from a young age (Compas et al, 1991).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition to research supporting the effects of maltreatment experiences, particularly sexual abuse, on the use of coping strategies (Bal et al, 2003;Hager & Runtz, 2012;Runtz & Schallow, 1997;Sabina & Tindale, 2008), these results indicated that psychologically maltreated adolescents use more maladaptive coping and less adaptive coping. This is consistent with previous studies (Bal et al, 2003;Flett et al, 2012;Hager & Runtz, 2012;Kraaij et al, 2003;Runtz & Schallow, 1997;Sabina & Tindale, 2008;Tremblay et al, 1999). Parent-child relationships play a significant role in the development of coping skills (Lerner et al, 2002), and children learn how to cope with stressful events from a young age (Compas et al, 1991).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, consistent with the present study, previous evidence supports the notion that active coping strategies are associated with better mental health and wellbeing, whereas avoidant coping strategies are related to various undesirable outcomes (Flett et al, 2012;Kraaij et al, 2003;Runtz & Schallow, 1997;Tremblay et al, 1999). The ability to cope and adapt to stressors is a central facet of individual development (Compas, Connor-Smith, Saltzman, Thomsen, & Wadsworth, 2001), and individuals use a variety of coping strategies in order to reduce or manage the physical, psychological, or social effects of stressful life events (Lazarus & Folkman, 1984).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Social support is a likely moderator in the relation between perfectionism and internalizing problems, but investigating which specific sources of social support (e.g., peers vs. teachers) buffer the association is an important next step. In one study of 58 adolescents with a history of abuse, Flett et al (2012) found maladaptive perfectionism to be significantly and negatively correlated to family support, but not peer or classmate support. This is the only known study to examine social support and perfectionism in a sample of adolescents.…”
Section: Support From Teachers and Classmatesmentioning
confidence: 99%
“…limitations and find appropriate coping methods (Flett, Druckman, Hewitt, & Wekerle, 2012), while maladaptive perfectionists are more likely to think dichotomously and are often driven by a fear of failure and disappointing others . Furthermore, the perceptions and cognitive styles of maladaptive perfectionists may differ from adaptive perfectionists.…”
mentioning
confidence: 99%